Demonstration and characterization of specific binding sites for factor VIII/von Willebrand factor on human platelets. - Kao, K J (1979)
The presence of specific Factor VIII/von Willebrand factor (FVIII/vWF) binding sites on human platelets has been demonstrated by using 125I-FVIII/vWF and washed human platelets. Binding is ristocetin-dependent and increases in proportion to the concentration of ristocetin from 0.2 to 1 mg/ml. Binding of 125I-FVIII/vWF to platelets can be competitively inhibited by unlabeled human or bovine FVIII/vWF, but not by human thrombin, fibrinogen, alpha 2-macroglobulin, equine collagen, or a lectin of Ricinus communis. Scatchard analysis of binding data indicated that the dissociation constant of FVIII/vWF receptors is 0.45--0.5 nM. There are 31,000 binding sites per platelet at 1 mg/ml of ristocetin concentration. The optimal pH range for binding is from 7.0 to 7.5. At a concentration of 2 mM, EGTA inhibits 86% of the binding; however, 20 mM of Ca++, Mg++, or EDTA have little effect. Binding sites for FVIII/vWF were found only on platelets, and no significant binding was detected with human erythrocytes or polymorphonuclear leukocytes.